Potential hypothalamic targets of relaxin-3 innervation: a perspective - Smith, Craig M.; Chua, Berenice E.; Walker, Andrew W.; Gundlach, Andrew L. (Italian Journal of Anatomy and Embryology, 2014)
Relaxin-3 is a recently identified neuropeptide transmitter primarily expressed by neurons of the pontine nucleus incertus, which binds/activates the Gi/o-protein coupled receptor, RXFP3. Functional studies have demonstrated that relaxin-3 modulates behavioural arousal in rodents, and although initial anatomical mapping studies have revealed relaxin-3-positive projections within several brain regions containing neurons that control behavioural arousal, further analysis of this topography has been hampered by the unavailability of a suitable specific RXFP3 antibody. In an effort to determine some of the neuron populations that relaxin-3 signalling directly modulates, we examined the distribution of relaxin-3 immunoreactive nerve fibres/ terminals within the mouse lateral hypothalamus (LH) and ventrolateral preoptic area (VLPO), relative to elements containing protein markers for arousal-related neurons. Within the LH, relaxin-3 fibres were predominately distributed more laterally than orexin immunoreactive neurons, in the so-called ‘parvalbumin-immunoreactive’ PV1 region; but direct contacts with these parvalbumin neurons were scarce. Within the VLPO, relaxin-3 fibres were observed in close contact with galanin-immunoreactive elements, but the soma of the galanin/GABA neurons in the area that project to and inhibit arousal-promoting neurons such as orexin/LH cells to promote sleep, were not identified under the conditions employed. Nonetheless, these preliminary studies suggest an interaction between relaxin-3 and VLPO galanin neurons that may contribute to the arousal-promoting action of relaxin-3.